PELAKSANAAN SISTEM OUTSOURCING DALAM HUKUM KETENAGAKERJAAN DI INDONESIA - Darwati; Verdita Kurniawan (Fakultas Hukum Universitas Borobudur, 2023)
Labor law in Indonesia is currently receiving a lot of attention, especially regarding the use of labor through third parties or outsourcing with a certain time work agreement system. Law Number 13 of 2003 concerning Employment regulates certain time work agreements in Article 59 and handing over part of the work to other parties in Article 64, as well as workers' rights being the same as other workers or in accordance with applicable laws and regulations as formulated in Article 65 paragraph (4). In this research, the issues discussed are outsourcing procedures that apply in Indonesia and legal protection for workers who use the outsourcing system in Indonesia. The methodology used is normative juridical and sociological juridical. The results of research on Law Number 13 of 2003 concerning Employment do not contain the term outsourcing, only handing over part of the work to other companies through work contracting agreements or labor service providers. Protection for workers who work for other companies with a fixed-term work agreement system is the same as other workers. Labor inspectors supervise the implementation of employment agreements and employment contracts. The suggestion for the government is to provide sanctions for violations committed by entrepreneurs and Law Number 6 of 2023 concerning Job Creation is recommended to be abolished.